ANALISIS KEBIJAKAN PENANGGULANGAN KEMISKINAN MELALUI PENDIDIKAN BOARDING SCHOOL SMK NEGERI 3 DI KABUPATEN PURBALINGGA - Sabani, Ivana Andi; ., Sulistyowati; Adnan, Muhammad (Journal of Politic and Government Studies, 2017)
Poverty is a classic problem of mankind in every part of the world andbecomes a complex issue because it is not just about low income. The low level ofeducation, skills, and the lack of introduction to technology are the human resourceconstraints that are closely related to the causes of poverty. Purbalingga regency isone of the areas with a high percentage of poor people who are always ranked in thepoorest areas in Central Java Province. The purpose of this research is to analyze thepolicy of poverty reduction by Purbalingga Government through establishment ofBoarding School of SMK Negeri 3 Purbalingga.This study uses mixed methods between qualitative and quantitative with aqualitative approach remains the main approach. Data collection techniques werecarried out, among others, by collecting documents and in-depth interviews withactors involved in the policy, and using a research questionnaire to the researchsubjects of alumni / boarding school graduate SMK Negeri 3 Purbalingga. Analysisof research data is done by combining primary data obtained and findings in bothqualitative and quantitative data.Based on the research that has been done, it is known that the policy has beenimplemented optimally, consistently, and there is a continuous suitability of visionamong policy actors in 3 different Heads of District (Bupati), and achievements thatcan penetrate TOP 35 in Public Service Innovation Competition (SiNovik) 2016.Quantitative data shows that there is an increase of living standards of alumni SMKNegeri 3 Purbalingga coming from poor families, as the object of poverty problem inPurbalingga Regency. This shows that policies that have the principle of breaking thepoverty chain have succeeded in reducing the number of poor people, thesustainability of the program is likely to reduce poverty significantly.Keywords: Poverty Reduction, Education Implementation Model, PolicyImplementation.